2015
DOI: 10.1186/s12913-016-1268-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the World Health Organization 8-steps in wheelchair service provision in wheelchair users in a less resourced setting: a cohort study in Indonesia

Abstract: BackgroundFor people who have a mobility impairment, access to an appropriate wheelchair is an important step towards social inclusion and participation. The World Health Organization Guidelines for the Provision of Manual Wheelchairs in Less Resourced Settings emphasize the eight critical steps for appropriate wheelchair services, which include: referral, assessment, prescription, funding and ordering, product preparation,fitting and adjusting, user training, and follow-up and maintenance/repairs. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 50 publications
5
74
0
5
Order By: Relevance
“…This could be due to several factors, such as the provision of a wheelchair that did not meet their needs, it did not fit properly to their body, lack of user and maintenance training, environmental barriers, or due to differences in the population. These findings are aligned with those of the study published by Toro et al [17] in Indonesia that suggested the positive impact of the WHO 8-steps in wheelchair provision.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This could be due to several factors, such as the provision of a wheelchair that did not meet their needs, it did not fit properly to their body, lack of user and maintenance training, environmental barriers, or due to differences in the population. These findings are aligned with those of the study published by Toro et al [17] in Indonesia that suggested the positive impact of the WHO 8-steps in wheelchair provision.…”
Section: Discussionsupporting
confidence: 91%
“…Our study population included subjects with a diverse set of disabilities, with Polio being most common (Table 2). The study by Toro et al [17] had similar conditions as our study in terms of the application of the WHO 8-Steps and also happened in Indonesia. However, their findings determined no significant differences in wheelchair skills between baseline and endline.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations